Microfluidic light-driven synthesis of tetracyclic molecular architectures - Mateos, Javier; Meneghini, Nicholas; Bonchio, Marcella; Marino, Nadia; Carofiglio, Tommaso; Companyó, Xavier; Dell’Amico, Luca (Beilstein Journal of Organic Chemistry, 2018)
Herein we report an effective synthetic method for the direct assembly of highly functionalized tetracyclic pharmacophoric cores. Coumarins and chromones undergo diastereoselective [4 + 2] cycloaddition reactions with light-generated photoenol intermediates. The reactions occur by aid of a microfluidic photoreactor (MFP) in high yield (up to >98%) and virtually complete diastereocontrol (>20:1 dr). The method is easily scaled-up to a parallel setup, furnishing 948 mg of product over a 14 h reaction time. Finally, a series of manipulations of the tetracyclic scaffold obtained gave access to valuable precursors of biologically active molecules.
Keywords: [4 + 2] photoenol; cycloaddition; flow chemistry; microfluidic photoreactor; photoredox catalysis; synthetic photochemistry

(untitled) - Ravelli, D.; Protti, S.; Fagnoni, M. (Chem. Rev., 2016)
See for a review.

(untitled) - Shaw, M. H.; Twilton, J.; MacMillan, D. W. C. (J. Org. Chem., 2016)

(untitled) - Zou, Y.-Q.; Hörmann, F. M.; Bach, T. (Chem. Soc. Rev., 2018)

(untitled) - Cambié, D.; Bottecchia, C.; Straathof, N. J. W.; Hessel, V.; Noël, T. (Chem. Rev., 2016)

(untitled) - Su, Y.; Straathof, N. J. W.; Hessel, V.; Noël, T. (Chem. – Eur. J., 2014)

(untitled) - Mateos, J.; Cherubini-Celli, A.; Carofiglio, T.; Bonchio, M.; Marino, N.; Companyó, X.; Dell’Amico, L. (Chem. Commun., 2018)

(untitled) - Sammes, P. G. (Tetrahedron, 1976)

(untitled) - Nicolaou, K. C.; Gray, D.; Tae, J. (Angew. Chem., Int. Ed., 2001)

(untitled) - Wright, P. M.; Seiple, I. B.; Myers, A. G. (Angew. Chem., Int. Ed., 2014)

(untitled) - Sandulache, A.; Silva, A. M. S.; Cavaleiro, J. A. S. (Tetrahedron, 2002)

(untitled) - Allred, T. K.; Manoni, F.; Harran, P. G. (Chem. Rev., 2017)

(untitled) - Bauvois, B.; Puiffe, M.-L.; Bongui, J.-B.; Paillat, S.; Monneret, C.; Dauzonne, D. (J. Med. Chem., 2003)

(untitled) - Su, Y.; Kuijpers, K.; Hessel, V.; Noël, T. (React. Chem. Eng., 2016)

(untitled) - Lantaño, B.; Aguirre, J. M.; Drago, E. V.; de la Faba, D. J.; Pomilio, N.; Mufato, J. D. (Magn. Reson. Chem., 2017)

(untitled) - Sook, O.; Jang, B. S. (Arch. Pharmacal Res., 1995)

(untitled) - Hanaya, K.; Onodera, S.; Ikegami, Y.; Kudo, H.; Shimaya, K. (J. Chem. Soc., Perkin Trans. 2, 1981)